How to ‘future proof’ benefit-sharing from the use of DSI in agricultural research and development - Halewood, Michael; Rouard, Mathieu; Sackville-hamilton, Ruaraidh; Sansaloni, Carolina; Reyes Herrera, Paula; Pinilla, Gustavo; Toledo, Alvaro (2024)
Recording of Genebank Initiative side event given at 2nd meeting of Ad Hoc Open-ended Working Group on Benefit-sharing from the Use of Digital Sequence Information on Genetic Resources, 13 August 2024.